RETRACTED: Does resource efficiency matter for environmental quality in Canada? - Kirikkaleli, Dervis; Castanho, Rui Alexandre; Deniz Özbay, Rahmi; Yilmaz Genc, Sema; Ahmed, Zahoor (Frontiers in Environmental Science, 2023)
In order to combat climate change, the OECD emphasized the need to minimize the environmental impact of material use, as well as promote resource efficiency and accelerate the creation of a circular economy. The present study objects to promote a new debate about Canadian environmental quality and resource efficiency. In other words, this paper aims to capture the effect of resource efficiency on environmental quality in Canada while controlling financial development, economic growth, and energy. Nonlinear ARDL bounds test results indicate the significant long-run linkage between environmental quality, resource efficiency, financial development, economic growth, and energy in Canada. Moreover, the asymmetric results underline that (i) resource efficiency mitigates environmental degradation; (ii) economic growth and energy uses in Canada significantly increase consumption-based CO2 emissions; (iii) financial development positively contributes to environmental stability. Therefore, policymakers in Canada make sure that circular economies and resource efficiency can help reach net zero and combat climate change.